2012
DOI: 10.1016/j.pain.2012.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Top-down attentional modulation of analgesia induced by heterotopic noxious counterstimulation

Abstract: Heterotopic noxious counterstimulation (HNCS) by the application of a sustained noxious stimulus has been shown to inhibit nociceptive processes and decrease pain induced by a competing noxious stimulus. However, it is still not clear how attentional processes contribute to these effects. The main objective of this study was to compare the analgesic effects of HNCS in 2 sessions during which top-down attention was manipulated. Acute shock pain and the nociceptive flexion reflex were evoked by transcutaneous el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 47 publications
2
49
1
2
Order By: Relevance
“…Illustrated on the right are plots of average regional D2/D3R activation in the areas showing significant D2/D3R activation in the entire sample (A) and in the area that showed a significant group ϫ condition interaction (B). sensitivity and tolerance have been associated with genetic polymorphisms related to DA system function (Treister et al, 2009;Jääskeläinen et al, 2014), whereas no change was found in these measures after experimental reductions in brain DA (Becker et al, 2013;Tiemann et al, 2014). Nonetheless, specifically regarding striatal DA D2/D3R function, [ 11 C]raclopride PET studies have found significant positive correlations between baseline striatal D2/D3R BP ND and pain sensitivity in HCs (Hagelberg et al, 2002;Scott et al, 2006) and in patients with FM, who showed significant positive correlations between striatal D2/D3R BP ND and measures of both experimental pain sensitivity and widespread tenderness (Wood et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Illustrated on the right are plots of average regional D2/D3R activation in the areas showing significant D2/D3R activation in the entire sample (A) and in the area that showed a significant group ϫ condition interaction (B). sensitivity and tolerance have been associated with genetic polymorphisms related to DA system function (Treister et al, 2009;Jääskeläinen et al, 2014), whereas no change was found in these measures after experimental reductions in brain DA (Becker et al, 2013;Tiemann et al, 2014). Nonetheless, specifically regarding striatal DA D2/D3R function, [ 11 C]raclopride PET studies have found significant positive correlations between baseline striatal D2/D3R BP ND and pain sensitivity in HCs (Hagelberg et al, 2002;Scott et al, 2006) and in patients with FM, who showed significant positive correlations between striatal D2/D3R BP ND and measures of both experimental pain sensitivity and widespread tenderness (Wood et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…sensitivity and tolerance have been associated with genetic polymorphisms related to DA system function (Treister et al, 2009;Jääskeläinen et al, 2014), whereas no change was found in these measures after experimental reductions in brain DA (Becker et al, 2013;Tiemann et al, 2014). Nonetheless, specifically regarding striatal DA D2/D3R function, [ 11 C]raclopride PET studies have found significant positive correlations between baseline striatal D2/D3R BP ND and pain sensitivity in HCs (Hagelberg et al, 2002;Scott et al, 2006) and in patients with FM, who showed significant positive correlations between striatal D2/D3R BP ND and measures of both experimental pain sensitivity and widespread tenderness (Wood et al, 2007). Together, these previous studies and the present data suggest that the interindividual variability in baseline striatal D2/D3R function may be an important factor in the development and persistence of generalized hyperalgesia in chronic musculoskeletal pain, which is a frequent finding not only in FM, but also in chronic back pain (Giesecke et al, 2004;O'Neill et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations